Characteristics of photonic nanojets from ordered microassemblies of dielectric spheres. (29th March 2016) - Geints, Yu E; Zemlyanov, A A; Panina, E K
Abstract: Spatially localised light structures (photonic nanojets) formed in the near field of light scattering from an ordered ensemble of single-layer clusters of transparent glass microspheres have been theoretically studied. The main parameters of photonic nanojets (length, width, focal distance and intensity) are calculated based on numerical solution of Maxwell equations, and their behaviour under conditions of interference between neighbouring microparticles is analysed. The degree of manifestation of collective effects during the formation of a nanojet array is found to depend on the spatial structure of the ensemble of microspheres, their size and repetition period. It is found that in some cases, having chosen an appropriate configuration of a microsphere ensemble, one can improve significantly the characteristics of the photonic nanojets formed by this ensemble.